The Deinstitutionalization of Persons with Psychosocial Disabilities from the Perspective of Ecological Systems Theory - Genienė, Rasa; Šumskienė, Eglė; Gevorgianienė, Violeta; Mataitytė-Diržienė, Jurga (Socialinė teorija, empirija, politika ir praktika, 2021)
The deinstitutionalization of social care in Lithuania started in 2012 after the adoption of the strategic guidelines by the Ministry of Social Security and Labour. The goal of this reform was to improve the care conditions and introduce new community-based services for persons with disabilities. Almost ten years of the reform resulted in only five percent of persons with disabilities who moved to community settings, mainly group-living homes. The slow-motion of the reform, as well as the tensions in the communities, suggests the need for a thorough analysis of the process of deinstitutionalization and its improvement. Bronfenbrenner’s ecological theory is applied as a conceptual and methodological tool for understanding the roles of deinstitutionalization agents at different levels, including the Ministry of Social Security and Labour, municipalities, non-governmental organizations, social care institutions, and local communities. All of these agents are involved and diversely interact among themselves during the transformation process of the social care system. The ecological theory provides the necessary integrated approach to the analysis of the process of deinstitutionalization of the social care system at the micro-, meso-, exo-, and macro levels. Deinstitutionalization and the trajectories of its participants reveal resilient connections with different fields of the ecological system and show that different system components not only represent different systems but become microsystems themselves that affect all elements in the ecological system. The complexity of environmental systems constitutes the basis of ecological systems theory. It serves as a lens to guide the analysis of the transformation of a particular person’s life in the context of deinstitutionalization. Herewith, it is an appropriate tool for understanding the impact of deinstitutionalization on specific local communities.